Nephroprotective mechanisms of Rhizoma Chuanxiong and Radix et Rhizoma Rhei against acute renal injury and renal fibrosis based on network pharmacology and experimental validation - Li, Jun; Li, Tonglu; Li, Zongping; Song, Zhiyong; Gong, Xuezhong (Frontiers in Pharmacology, 2023)
This study investigated the molecular mechanisms of Rhizoma Chuanxiong (Chuanxiong, CX) and Radix et Rhizoma Rhei (Dahuang, DH) in treating acute kidney injury (AKI) and subsequent renal fibrosis (RF) by applying network pharmacology and experimental validation. The results showed that aloe-emodin, (-)-catechin, beta-sitosterol, and folic acid were the core active ingredients, and TP53, AKT1, CSF1R, and TGFBR1 were core target genes. Enrichment analyses showed that the key signal pathways were the MAPK, IL-17, and HIF-1 signaling pathways. In vivo experiments confirmed that CX and DH pretreatment significantly inhibited the levels of SCr, BUN, UNAG, and UGGT in contrast media-induced AKI (CIAKI) rats (p < 0 001). The results of western blot showed that compared with the control group, the protein levels of p-p38/p38 MAPK, p53 and Bax in the CIAKI group were significantly increased, and the levels of Bcl-2 were significantly reduced (p < 0.001). CX and DH interventions significantly reversed the expression levels of these proteins (p < 0.01). The localization and quantification of p-p53 expression in immunohistochemistry technology also support the above results. In conclusion, we demonstrated that CX and DH may modulate the inflammatory response, cell death, and cell cycle processes in AKI and RF. Our data also suggest that CX and DH may inhibit tubular epithelial cell apoptosis and improve AKI by inhibiting p38 MAPK/p53 signaling.